2020
DOI: 10.1021/acsbiomaterials.0c01507
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Solubilized Human Hair Keratins

Abstract: Human hair keratins have proven to be a viable biomaterial for diverse regenerative applications. However, the most significant characteristic of this material has not been exploited, that is the ability to self-assemble into nanoscale intermediate filaments. Herein, we successfully demonstrated the induction of hair-extracted keratin self-assembly in vitro to form dense, homogenous and continuous nanofibrous networks. These networks remain hydrolytically stable in vitro for up to 5 days in complete cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the current study, TMT-based quantitative proteomics revealed that 4,994 proteins were obtained in all samples, and 50 proteins were denoted as candidate genes for wool growth based on differential analysis. In addition, the DEPs were associated with keratin filament, peptidase regulator activity, animal organ development, and membrane lipid metabolic process, which has been reported in other species like human (Lai et al, 2021) and goat (Gao et al, 2016). Based on KEGG pathway enrichment some pathways related to wool growth and hair follicle development were identified, such as Protein digestion and absorption, Fatty acid biosynthesis, ECMreceptor interaction and PI3K-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 74%
“…In the current study, TMT-based quantitative proteomics revealed that 4,994 proteins were obtained in all samples, and 50 proteins were denoted as candidate genes for wool growth based on differential analysis. In addition, the DEPs were associated with keratin filament, peptidase regulator activity, animal organ development, and membrane lipid metabolic process, which has been reported in other species like human (Lai et al, 2021) and goat (Gao et al, 2016). Based on KEGG pathway enrichment some pathways related to wool growth and hair follicle development were identified, such as Protein digestion and absorption, Fatty acid biosynthesis, ECMreceptor interaction and PI3K-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, keratin-based biomaterials have an intrinsic ability to support cellular proliferation and can be used as sponges, films, and hydrogels for various biomedical applications. These are all possibilities that, to be explored, require a complete characterization of keratin waste, such as that performed on human hair keratin in [ 36 ]. Those applications should combine the well-known basic properties of the raw material into composites having the merit to offer sufficient mechanical and interface performance, needed for its industrial process.…”
Section: Resultsmentioning
confidence: 99%
“…[ 45,46 ] These self‐assemblies of hard keratins or soft (cellular) keratins are typically hetero‐assembly, which requires a type I keratin with its pairing type II keratin. [ 44 ] Our work demonstrated that QTY variant keratins had the characteristics of heterotypic self‐assembly and homotypic self‐assembly, which further improved their uses in more biomedical applications. The native sequences of keratins contain a large amount of cysteine, glycine, and proline, a low content of lysine and methionine, and almost no tryptophan.…”
Section: Discussionmentioning
confidence: 88%
“…The mechanics of these hierarchical composites are controlled by the self-assembly of keratins. [1,44] Besides, the formation of cytoskeletal IF in soft epithelia is also dependent on the assembly of cellular keratins. [45,46] These self-assemblies of hard keratins or soft (cellular) keratins are typically hetero-assembly, which requires a type I keratin with its pairing type II keratin.…”
Section: Discussionmentioning
confidence: 99%